Primordial black holes as dark matter: constraints from compact ultra-faint dwarfs. Issue 1 (10th January 2018) - Zhu, Qirong; Vasiliev, Eugene; Li, Yuexing; Jing, Yipeng
Abstract: The ground-breaking detections of gravitational waves from black hole mergers by LIGO have rekindled interest in primordial black holes (PBHs) and the possibility of dark matter being composed of PBHs. It has been suggested that PBHs of tens of solar masses could serve as dark matter candidates. Recent analytical studies demonstrated that compact ultra-faint dwarf galaxies can serve as a sensitive test for the PBH dark matter hypothesis, since stars in such a halo-dominated system would be heated by the more massive PBHs, their present-day distribution can provide strong constraints on PBH mass. In this study, we further explore this scenario with more detailed calculations, using a combination of dynamical simulations and Bayesian inference methods. The joint evolution of stars and PBH dark matter is followed with a Fokker–Planck code phaseflow . We run a large suite of such simulations for different dark matter parameters, then use a Markov chain Monte Carlo approach to constrain the PBH properties with observations of ultra-faint galaxies. We find that two-body relaxation between the stars and PBH drives up the stellar core size, and increases the central stellar velocity dispersion. Using the observed half-light radius and velocity dispersion of stars in the compact ultra-faint dwarf galaxies as joint constraints, we infer that these dwarfs may have a cored dark matter halo with the central density in the range of 1–2 M⊙ pc − 3, and that the PBHs may have a mass range of 2–14 M⊙ if they constitute all or a substantial fraction of the dark matter.